3D-printed weight holders design and testing in mouse models of spinal cord injury - Sara De Vincentiis; Sara De Vincentiis; Francesca Merighi; Francesca Merighi; Peter Blümler; Jose Gustavo De La Ossa Guerra; Mariachiara Di Caprio; Marco Onorati; Marco Mainardi; Marco Mainardi; Vittoria Raffa; Marina Carbone; et al. (Frontiers Media S.A., 2024)
This paper details the comprehensive design and prototyping of a 3D-printed wearable device tailored for mouse models which addresses the need for non-invasive applications in spinal cord studies and therapeutic treatments. Our work was prompted by the increasing demand for wearable devices in preclinical research on freely behaving rodent models of spinal cord injury. We present an innovative solution that employs compliant 3D-printed structures for stable device placement on the backs of both healthy and spinal cord-injured mice. In our trial, the device was represented by two magnets that applied passive magnetic stimulation to the injury site. This device was designed to be combined with the use of magnetic nanoparticles to render neurons or neural cells sensitive to an exogenous magnetic field, resulting in the stimulation of axon growth in response to a pulling force. We show different design iterations, emphasizing the challenges faced and the solutions proposed during the design process. The iterative design process involved multiple phases, from the magnet holder (MH) to the wearable device configurations. The latter included different approaches: a "Fitbit", "Belt", "Bib", and ultimately a "Cape". Each design iteration was accompanied by a testing protocol involving healthy and injured mice, with qualitative assessments focusing on animal wellbeing. Follow-up lasted for at least 21 consecutive days, thus allowing animal welfare to be accurately monitored. The final Cape design was our best compromise between the need for a thin structure that would not hinder movement and the resistance required to maintain the structure at the correct position while withstanding biting and mechanical stress. The detailed account of the iterative design process and testing procedures provides valuable insights for researchers and practitioners engaged in the development of wearable devices for mice, particularly in the context of spinal cord studies and therapeutic treatments. Finally, in addition to describing the design of a 3D-printed wearable holder, we also outline some general guidelines for the design of wearable devices.